A kinetic comparison between E2P and the E2P-like state induced by a beryllium fluoride complex in the Na,K-ATPase. Interactions with Rb+ - Faraj, Santiago Enrique (2019)
Metal-fluoride complexes have been used to induce E2P-like states with the aim of studying the events that occur during E2P hydrolysis in P-type ATPases. In the present work, we compared the E2P-like state induced by a beryllium fluoride complex (BeFx) with the actual E2P state formed through backdoor phosphorylation of the Na,K-ATPase. Formation of E2P and E2P-like states were investigated employing the styryl dye RH421. We found that BeFx is the only fluorinated phosphate analog that, like Pi, increases the RH421 fluorescence. The observed rate constant, kobs, for the formation of E2P decreases with [Pi] whereas that of E2BeFx increases with [BeFx]. This might wrongly be taken as evidence of a mechanism where the binding of BeFx induces a conformational transition. Here, we rather propose that, like for Pi, binding of BeFx follows a conformational-selection mechanism, i.e. it binds to the E2 conformer forming a complex that is much more stable than E2P, as seen from its impaired capacity to return to E1 upon addition of Na+. Although E2P and E2BeFx are able to form states with 2 occluded Rb+, both enzyme complexes differ in that the affinity for the binding and occlusion of the second Rb+ is much lower in E2BeFx than in E2P. The higher rates of Rb+ occlusion and deocclusion observed for E2BeFx, as compared to those observed for other E2P-like transition and product states suggest a more open access to the cation transport sites, supporting the idea that E2BeFx mimics the E2P ground state.